Automated static structural FEA environment in MATLAB using Solid Edge and Femap - Szántó, András (International Journal of Engineering and Management Sciences, 2019)
Nowadays, CAD and FE software are getting integrated to each other. However, these new integrated pieces of software cannot be customized enough to analyze different optimization methods or model behavior. In this paper, a MATLAB environment is developed that connects to C# and VB programs, which use Solid Edge and Femap API functions, in order to automate the geometry modification and the FE model building and solving functions. A simple static structural size optimization problem is solved with the fmincon solver of MATLAB.